The relationship between management accounting, profitability and operations in an uncertain world. Evidence from literature and practice - Smith, Philip (Cranfield University, 2007)
At the heart of many core Management Accounting (MA) practices there is a potential mismatch between the assumption of a materially predictable future operating environment, and the reality of an uncertain and unpredictable world. Practices such as budgets, product costing, investment appraisal and financial projections, aimed at facilitating the achievement of profitability goals, are based on the assumption that the future is sufficiently stable and predictable to benefit from analytical calculation. However, we live in a world where the future can be uncertain, unstable and unpredictable. Does this mean that when operating conditions become unstable, unpredictable and uncertain many MA practices lose their core modus operandi? This thesis addresses this issue through an interwoven mix of a longitudinal case study and literature reviews spread over three projects. The case study was longitudinal and based on in depth participant observation. The firm involved was a £38m UK logistics company. The study benefited from totally unrestricted access to all strategic, financial and operational activities and data, because of the author’s senior role in the firm. The literature review was conducted using a targeted systematic review (Tranfield and Denyer, 2003) supported by additional narrative reviews. This synoptic paper provides a reflective synthesis of the findings and the contribution of the three projects which together constitute the research. Four core interlinked findings emerged from the study, based on the assumption that the achievement of profitability goals is the primary goal of the organisation. First, building on the proposals of (Otley, 1999) a framework showing the relationship between MA, profitability, operations and uncertainty is proposed. It demonstrates how MA financialises operations by creating a parallel financial space to the operational space; how profitability outcomes result from the financial consequences of operational actions; how the role of MA is to inform and control operational actions in a manner that achieves profitability goals; and how uncertainty has a critical impact on MA functionality. Second, the differing dimensions and implications of uncertainty are distinguished. The principal distinction is between external and internal uncertainty. External uncertainties arise from unanticipated changes from customers, suppliers and the market and thus affect the predictability of the future on which plans and targets are based. The data gathered during the course of this research suggests that external uncertainty tends to be typified by pockets of instability oscillating with periods of relative stability. Internal uncertainties occur in relation to management effectiveness, reporting validity and choice of appropriate accounting perspective (five are identified - Product, Customer, Throughout, Process, Financial Accounting). The external uncertainties magnify the impact of the internal uncertainties by potentially changing and thus de-stabilising the requirements of management, the validity of reporting and the appropriateness of the accounting perspective used. Third, Management Accounting Systems (MAS) respond to external uncertainties, and the aspirations of external financial stakeholders for increased profitability, by operating in two differing modes – the first is fixed/control (Fixed), the second is inform/flex (Flex). Fixed is the default mode and assumes conditions of relative certainty; the role is to control the achievement of agreed plans and targets. Flex is intermittently initiated when, signalled by feedback, the impact of external uncertainties or profit pressures trigger the need to change original plans and targets. Calculative analysis informs revised operational plans aimed at maintaining the achievement of profitability goals; targets are flexed to reflect the changes. The intent is to develop a revised position of relative stability in which the achievement of profitability plans and targets can be controlled via reverting back to Fixed. The process is therefore continual, but appears to be typified by an uneven series of oscillations between the two modes. Four, the Financial Accounting (FA) profitability measure, with the goal derived from external financial stakeholders, provides partial responses to the three internal uncertainties by introducing for each an element of certainty. For management effectiveness uncertainty, the profitability goal provides a relatively certain external referent which can be cascaded down the organisational structure, and against which performance can be evaluated. For reporting validity uncertainty, FA standards provide an authoritatively accepted definition of profitability, so that reported profitability is treated as if it were ‘true and fair’. For multiple accounting perspectives uncertainty, four perspectives (Product, Customer, Throughout, Process) make up a range of MA tools for developing actions to achieve target profitability levels, and the fifth (FA) provides the definition of profitability; all five are complementary and compatible as their differing aggregations are composed of the same underlying financial transactions. These responses, however, are only partial as the aspirations of external financial stakeholders are in themselves substantially self referential and liable to change, and the underlying uncertainty of FA reporting validity still exists, even if treated as if it does not. The study contributes to the further development of MA theory. It extends the Otley (1999) framework towards linking operations and profitability through parallel operational and financial spaces, and incorporating the central role of uncertainty. It adds to the debate in MA research on uncertainty by providing a classification of its dimensions, and its impact on triggering a requirement for differing MA modes. It highlights the central role of profitability in providing a stable certainty of purpose as a counterbalance to inherent internal and external uncertainties. It provides a clear identification of the differences and complementarities between MA and FA, FA defining the quantum of profitability achieved, MA facilitating the achievement of profitability goal. Finally the study inputs to a wide range of issues addressed by MA research which at their heart reflect the impact of uncertainty (Budgeting, Accounting Representation, Costing Perspectives). The study contributes to practice by proposing a set of ten tenets designed to provide guidelines for MAS development, implementation and evaluation. These are drawn from a cross sectional deconstruction of the four findings, viewed as a whole, aimed at identifying the specific factors that have direct implications for practice. The intent is that these tenets provide a bridge between theory and practice, based on the premise that, since MA theory was drawn from practice, the test of MA theory development is its applicability and relevance to practice.